Ethnoveterinary Remedies Used in Avian Complementary Medicine in Selected Communal Areas in Zimbabwe - Jambwa, Prosper; Katsande, Simbarashe; Matope, Gift; McGaw, Lyndy J. (Planta Medica, 2021)
Plant remedies used in avian ethnomedicine are potential candidates for the development of phytogenic feed additives. An ethnoveterinary survey was carried out in 3 districts in Zimbabwe to document plants used in poultry ethnomedicine and identify plants that have the potential to be used for the development of poultry phytogenic feed additives. The survey employed questionnaire-guided oral interviews with 146 smallholder farmers. Key areas of investigation and discussion were poultry production and traditional knowledge in bird health care (ethnotreatments and poultry disease control). The survey documented a total of 36 plant species cited as being useful interventions for the treatment and management of various poultry ailments/health constraints. These medicinal plants belonged to 22 families, with the Fabaceae family the dominant family. The plant species were used to treat 11 disease/health constraint categories, with the highest number of species being used for coccidiosis. Trees (44.44%) were the main reservoir of medicinal plants followed by herbs (36.11%), shrubs (8.33%), climbers (8.33%), and flowers (2.78%). Based on the results of the survey, Bobgunnia madagascariensis, Aloe chabaudii, Adenia gummifera, Erythrina abyssinica, Agave sisalana, Capsicum frutescens, Strychnos cocculoides, Aloe greatheadii, Tridactyle bicaudata, Senna singueana, Sarcostemma viminale, Morus alba, and Moringa oleifera are potential candidates for the development of phytogenic feed additives.
Keywords: poultry; ethnoveterinary medicine; phytogenic feed additives; therapeutic; antimicrobial resistance